Adenosine protects against indomethacin-induced gastric damage in rats - (:unkn) unknown (PLENUM PUBL CORP, 1998)
This study examines the putative gastroprotective effect of adenosine on indomethacin-induced gastric lesions and the possible mechanisms involved. After 24 hr of starvation, the rats were treated either with indomethacin (Indo; 25 mg/kg, subcutaneously) alone or adenosine + Indo (Ado; 7.5 mg/kg, subcutaneously, three times a day), or the vehicle (5% NaHCO3, subcutaneously). The length of hemorrhagic lesions in the stomachs was expressed as the lesion index. The tissue-associated myeloperoxidase (MPO) activity and protein oxidation were measured in gastric tissue samples. Formation of reactive oxygen species in gastric tissues was measured by using luminol- and lucigenin-enhanced chemiluminescence. In other groups of rats, gastric mucosal permeability and gastric acid output were performed following the same treatment regimens. The gastric mucosal permeability was measured by determination of [Cr-51]EDTA clearance in a perfused stomach preparation and gastric acid secretion studies were performed following pylorus ligation. The lesion index, the increase in lucigenin-enhanced chemiluminescence, and the increase in gastric mucosal permeability in Indo-treated rats were reversed by Ado pretreatment. Ado pretreatment also prevented the increase in gastric acid output and gastric volume in Indo-treated rats. Thus, these findings implicate that exogenous adenosine has a protective role on indomethacin-induced gastric lesions, possibly by inhibiting gastric hyperacidity and reactive oxygen formation and by preventing disruption of the mucosal integrity.
Keywords: adenosine; indomethacin; gastric injury; mucosal permeability; neutrophil; chemiluminescence; NONSTEROIDAL ANTIINFLAMMATORY DRUGS; OXYGEN METABOLITE PRODUCTION; ACID-SECRETION; ULCER FORMATION; MUCOSAL; INHIBITION; RECEPTOR; NEUTROPHILS; ACTIVATION